2013
DOI: 10.7150/ijbs.6427
|View full text |Cite
|
Sign up to set email alerts
|

Production of Polyploids and Unreduced Gametes in Lilium auratum × L. henryi Hybrid

Abstract: Intergenomic F1 hybrids between L. auratum x L. henryi and their BC1 progeny were investigated through genomic in situ hybridization technique (GISH) to determine their potential value in lily breeding. We confirmed that F1 intergenomic hybrids possessed a set of chromosomes (x=12) from both parents and that flowers of the F1 auratum × henryi hybrid showed an intermediate morphological phenotype. Pollen size, viability and germination ability were measured through microscopic observations. F1 intergenomic hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…2014 ). Additionally, Chung et al . (2013) reported that when the BC 1 plants (OOT) derived from the cross of the Oriental × Auratum Henryi hybrids were used as the female, subsequent BC 2 progeny was obtained, whereas no BC 2 plants were obtained in the reciprocal cross.…”
Section: Interspecific Hybridization and Genetic Background In Liliesmentioning
confidence: 99%
See 3 more Smart Citations
“…2014 ). Additionally, Chung et al . (2013) reported that when the BC 1 plants (OOT) derived from the cross of the Oriental × Auratum Henryi hybrids were used as the female, subsequent BC 2 progeny was obtained, whereas no BC 2 plants were obtained in the reciprocal cross.…”
Section: Interspecific Hybridization and Genetic Background In Liliesmentioning
confidence: 99%
“…Many intersectional hybrids producing 2 n pollen were selected and used extensively to produce BC 1 progeny in different backcross combinations to diploid cultivars (AA × OA; OA × AA; OO × OA; LA × AA; OO × LA; AA × LA; OO × OT; OT × OO and Martagon × Asiatic (MA) hybrid × AA) and to tetraploid cultivars in the combination OAOA × OA ( Barba-Gonzalez et al . 2005a , 2005b , 2006b , Chung et al . 2013 , Lim et al .…”
Section: Interspecific Hybridization and Genetic Background In Liliesmentioning
confidence: 99%
See 2 more Smart Citations
“…Allotriploid lilies are a main trend of modern lily breeding. They are obtained from BC 1 progeny of distant interspeci c F1 hybrids, because such F1 hybrids can produce small amount of functional 2n gametes and nonfunctional aueploid or n gametes due to abnormal meiosis [11][12][13][14][15][16][17][18][19][20][21]. In some cases, the sterile F1 hybrids were induced to become allotetraploid using oryzalin and colchicine to restore their fertility [22], then allotriploids are obtained through 4x × 2x or 2x × 4x [19].…”
Section: Introductionmentioning
confidence: 99%